Cost of illness of inflammatory bowel disease in the UK: a single centre retrospective study. Issue 10 (10th September 2004) - Bassi, A; Dodd, S; Williamson, P; Bodger, K
Abstract : Background and aims: The potentially high costs of care associated with inflammatory bowel disease (IBD) are recognised but we have little knowledge of the scale, profile, or determinants of these costs in the UK. This study aimed to describe costs of illness for a group of IBD patients and determine factors associated with increased healthcare costs. Setting: A university hospital serving a target population of approximately 330 000. Patients and methods: A six month cohort of IBD patients receiving any form of secondary care was identified, comprising 307 cases of ulcerative (or indeterminate) colitis and 172 cases of Crohn's disease. Demographic and clinical data were abstracted from clinical records and individual resource use was itemised for all attributable costs (including extraintestinal manifestations). Item costs were derived from national and local sources. Cost data were expressed as mean six month costs per patient (with 95% confidence interval (CI)) obtained using non-parametric bootstrapping. Determinants of cost were analysed using generalised linear regression modelling. A postal survey of patients was undertaken to examine indirect costs, out of pocket expenses, and primary care visits. Results: Inpatient services (medical and/or surgical) were required by 67 patients (14%) but accounted for 49% of total secondary care costs. Drug costs accounted for less than a quarter of total costs. Individual patient costs ranged from £73 to £33 254 per six months. Mean (95% CI) six month costs per patient were £1256 (£988, £1721) for colitis and £1652 (£1221, £2239) for Crohn's disease. Hospitalisation, disease severity grade, and disease extent correlated positively with cost of illness but costs were independent of age or sex. Compared with quiescent cases of IBD, disease relapse was associated with a 2–3-fold increase in costs for non-hospitalised cases and a 20-fold increase in costs for hospitalised cases. Survey data suggested average six month costs were <£30 per patient for primary care visits (both diseases) and median loss of earnings were £239 for colitis and £299 for Crohn's disease. Conclusions: This study represents the first detailed characterisation of the scale and determinants of costs of illness for IBD in a British hospital. Hospitalisation affected a minority of sufferers but accounted for half of the total direct costs falling on the healthcare system.